KINERJA PERANGKAT DESA DALAM MENJALANKAN TUGAS DAN WEWENANGNYA SESUAI UU NO. 6 TAHUN 2014 TENTANG DESA DI DESA TOPANG KECAMATAN RANGSANG KABUPATEN KEPULAUAN MERANTI - jurnalmap map; Rubaidah ÔÇÄ; Indra Prasetyo; Sri Mulyani (MAP (Jurnal Manajemen dan Administrasi Publik), 2021)
The village government is the smallest unit in the regional government structure, the village government has its own duties and authorities which are regulated by law. The main substance that has not changed is that the village government is the administrator of government at the village level. The purpose of this study was to see how the duties and functions of the village head and village officials in carrying out their duties and authorities in accordance with Law No. 6 of 2014 in the village of Topang, District. The type of research used is qualitative with descriptive method. Sources of data come from interviews and documentation studies. The results of the study indicate that the implementation of the main tasks and functions of the village and village apparatus is carried out in accordance with the provisions of the applicable laws and regulations. On the implementation side of the main tasks and functions of each village apparatus, it is necessary to be supported by human resources (HR) and adequate infrastructure in carrying out tasks and in order to achieve community services.